2004
DOI: 10.1023/b:jogc.0000018822.56297.a6
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and Long‐Term Impact of Receiving Genetic Mutation Results in Women at Increased Risk for Hereditary Breast Cancer

Abstract: Forty-seven unaffected women from high-risk breast cancer families who had received results for hereditary breast/ovarian predisposition genes between 1 month and 5 years ago were interviewed regarding their experiences. Women responded to open-ended questions. The initial emotional turmoil reported by most was generally short lived. However, the impact of genetic testing went beyond the individual to the extended family and social context, particularly in the short-term. A common theme was the difficulty asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 19 publications
7
50
0
Order By: Relevance
“…With the responsibility to inform family members follows decisions about whether contact should be taken with relatives of diseased family members, which family member is best suited and willing to deliver the news, and choosing the right time. Unaffected women in families with hereditary breast cancer have, in line with our findings, reported that the impact of genetic testing extends to family members and social contexts (Lim et al, 2004). Family members are perceived as the best informants, but support in this process from health care is commonly requested (Pentz et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…With the responsibility to inform family members follows decisions about whether contact should be taken with relatives of diseased family members, which family member is best suited and willing to deliver the news, and choosing the right time. Unaffected women in families with hereditary breast cancer have, in line with our findings, reported that the impact of genetic testing extends to family members and social contexts (Lim et al, 2004). Family members are perceived as the best informants, but support in this process from health care is commonly requested (Pentz et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression. 12,33,67 Some studies indicate that HNPCC carriers will first experience an immediate (2-4 weeks) but temporary increase in general anxiety after result disclosure.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…The notion of a ''genetic self'' has been described by Read et al [23] and Schild [22,24] who introduced the notion of a ''genetic identity'' [23][24][25]. A qualitative study [26] found that although the majority of women carrying mutations for cancer did not report a change in lifestyle, some women experience a sense of ''living with cancer'' throughout their lifetime, and mutation-negative women described ''feeling normal for the first time''. Other documented reports include a reevaluation of life priorities [26,27].…”
Section: Psychosocial Adjustment In Fapmentioning
confidence: 99%
“…A qualitative study [26] found that although the majority of women carrying mutations for cancer did not report a change in lifestyle, some women experience a sense of ''living with cancer'' throughout their lifetime, and mutation-negative women described ''feeling normal for the first time''. Other documented reports include a reevaluation of life priorities [26,27]. Reactions can also include a need to prepare emotionally for the time of illness, a loss of innocence and a sense of ongoing intrusive thoughts about health [26,28].…”
Section: Psychosocial Adjustment In Fapmentioning
confidence: 99%